A GESTÃO ESCOLAR E A IMPLEMENTAÇÃO DA BNCC: o caso de um município no Mato Grosso do Sul – MS - Janete Aparecida Coelho (2024)
The present research aims to analyze the changes that occurred in school management following the implementation of the National Common Curricular Base (BNCC), the municipality of Bataguassu, located in the state of Mato Grosso do Sul (MS), was chosen as the locus of the investigation. , has a time frame from 2017 to 2022 and takes place within the scope of the Postgraduate Program at UFMS-Campus de Três Lagoas/MS, in the line of research Teacher Training and Public Policies. It is anchored in the theoretical perspective proposed by Saviani, Libâneo, Oliveira and Toschi, Cury, Heloisa Lück and Paro, among other authors. In methodological terms, the research is presented from the perspective of historical-dialectical materialism, with a qualitative approach, with a descriptive and exploratory character supported by documentary analysis. The research results demonstrate that there is a neoliberal capitalist logic underway in the field of school management aimed at disseminating actions and documents to school leaders in order to shape them to act in accordance with the guidelines brought by the BNCC, making them mere applicators of the standard and supervisors of teaching actions with a view to complying with the Base. Keywords: Education; School Management; BNC-Director; BNCC; Mato Grosso do Sul.